Quantum cognition and decision theories: A tutorial - Yearsley, James M.; Busemeyer, Jerome R. (Journal of mathematical psychology, 2016)
Models of cognition and decision making based on quantum theory have been the subject of much interest recently. Quantum theory provides an alternative probabilistic framework for modelling decision making compared with classical probability theory, and has been successfully used to address behaviour considered paradoxical or irrational from a classical point of view. The purpose of this tutorial is to give an introduction to quantum models, with a particular emphasis on how to build these models in practice. Examples are provided by the study of order effects on judgements, and we will show how order effects arise from the structure of the theory. In particular, we show how to derive the recent discovery of a particular constraint on order effects implied by quantum models, called the Quantum Question (QQ) Equality, which does not appear to be derivable from alternative accounts, and which has been experimentally verified to high precision. However the general theory and methods of model construction we will describe are applicable to any quantum cognitive model. Our hope is that this tutorial will give researchers the confidence to construct simple quantum models of their own, particularly with a view to testing these against existing cognitive theories. •We present a tutorial on quantum models of cognition and decision aimed at those with little or no prior experience of such models.•We focus on the question of how to build quantum models in practice.•We give examples from the study of order effect, including a new derivation of the QQ Equality.